2018
DOI: 10.1152/ajpcell.00186.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of aquaporin-5 in noncancerous epithelial MDCK cells changes cellular morphology and actin fiber formation without inducing epithelial-to-mesenchymal transition

Abstract: Aquaporin-5 (AQP5) is a plasma membrane water channel mainly expressed in secretory glands. Increased expression of AQP5 is observed in multiple cancers, including breast cancer, where high expression correlates with the degree of metastasis and poor prognosis. Moreover, studies in cancer cells have suggested that AQP5 activates Ras signaling, drives morphological changes, and in particular increased invasiveness. To design intervention strategies, it is of utmost importance to characterize and dissect the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Epithelial cells undergoing EMT gain motility and invasiveness, which are characteristic features of metastatic cells (57), and AQP5 knockdown in various cancer cells indicated that AQP5 overexpression promotes EMT (9,58). However, our data indicate that AQP5 regulation of adhesion proteins in MDCK cells, a noncancerous cell line, is independent of EMT (10). Although the role of AQPs in cancer cell motility is well established, the full extent of the cellular changes triggered by AQP overexpression as well as the mechanisms inducing cancer cell motility is still elusive.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Epithelial cells undergoing EMT gain motility and invasiveness, which are characteristic features of metastatic cells (57), and AQP5 knockdown in various cancer cells indicated that AQP5 overexpression promotes EMT (9,58). However, our data indicate that AQP5 regulation of adhesion proteins in MDCK cells, a noncancerous cell line, is independent of EMT (10). Although the role of AQPs in cancer cell motility is well established, the full extent of the cellular changes triggered by AQP overexpression as well as the mechanisms inducing cancer cell motility is still elusive.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that overexpression of some AQPs in cancer cells, especially AQP5, aggravated epithelial-mesenchymal transition (EMT) and increased cancer cell migration (7)(8)(9). However, we recently showed that overexpression of AQP5 in Madin-Darby canine kidney (MDCK) cells, a noncancerous epithelial cell line, did not increase levels of the mesenchymal marker vimentin, even though it facilitated a decrease of the epithelial marker E-cadherin (10). Thus, the AQP5-mediated decrease in E-cadherin levels in MDCK cells was not associated with EMT, highlighting discrepancies in AQP5associated phenotypes between normal epithelial cells and ABBREVIATIONS: 3T3, 3-d transfer, inoculum 3 3 10 5 ; AQP, aquaporin; AQP3 LD5 , AQP3 with an AQP5 loop D substitution; AQP3 Tail5 , AQP3 with an AQP5 tail substitution; BSA, bovine serum albumin; EGF, epidermal growth factor; EGFP, enhanced green fluorescent protein; EMT, epithelial-mesenchymal transition; FBS, fetal bovine serum; FISH, fluorescence in situ hybridization; GFP, green fluorescent protein; HEK, human embryonic kidney; IRES, internal ribosome entry site; MDCK, Madin-Darby canine kidney; PFA, paraformaldehyde; PIV, particle image velocimetry; SSC, saline sodium citrate; ZO1, zonula occludens-1 different cancer cells.…”
mentioning
confidence: 86%
See 3 more Smart Citations